Everyday Practices and Activities to Improve Pre-school Self-Regulation: Cluster RCT Evaluation of the PRSIST Program - Howard, Steven J.; Vasseleu, Elena; Batterham, Marijka; Neilsen-Hewett, Cathrine (Frontiers in Psychology, 2020)
The Preschool Situational Self-Regulation Toolkit (PRSIST) Program was developed as a low-cost and embedded approach for educators to foster pre-schoolers’ self-regulation and related abilities (e.g., executive function, school readiness). This study reports on a cluster RCT study with 50 Australian pre-school services to evaluate the effectiveness of the PRSIST Program for improving children’s self-regulation, executive function and school readiness, compared to current routine practice. Pre-school centres were recruited to reflect the breadth of geography, pedagogical quality and socio-economic catchment areas across the early childhood education and care sector. All children identified as in their final year of pre-school education at these centres were invited to participate, resulting in a sample of 473 3-5-year-old children at baseline. Centres were randomly assigned to groups after baseline data collection, and data collectors were blinded to group assignment throughout the study. It was hypothesised that engagement in the PRSIST Program would improve children’s self-regulation, executive function and school readiness, over and above normal age-related rates of development. Results indicated small but significant improvements in executive functioning for the intervention group, after adjusting for cluster, baseline results and key covariates. All other outcomes were descriptively in favour of the intervention group but failed to reach significance. Levels of use of the program remained high by most educators throughout the intervention period, suggesting its acceptability and sustainability within these contexts. Together, results show promise for this approach to self-regulation development. Opportunities that might further strengthen this approach are discussed. This study was registered with the Australia and New Zealand Clinical Trials Registry (ACTRN12617001568303) and study protocols published in advance of commencement. Funding for this study was provided by the Australian Research Council’s Discovery Early Career Researcher Award research grant scheme.